Ultra-endurance triathlon racing increases haemoglobin mass: anti-doping implications - Gough, C. E.; Eastwood, A.; Fowler, P. M.; Vaile, J.; Saunders, P. U.; Anson, J.; Gore, C. J. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Introduction Seasonal variability of total body haemoglobin mass (tHb-mass) in elite athletes, as measured using the optimised carbon monoxide (CO) re-breathing method [1], is less than the variability in tHb-mass associated with blood doping [2]. Consequently, the World Anti-Doping Authority (WADA) is considering incorporating tHb-mass into the "athlete blood passport", which allows longitudinal monitoring of an athlete`s blood profile to enable detection of abnormal variations indicative of blood manipulation. Before tHb-mass can be used as an anti-doping aid, the stability of tHb-mass during racing must be similar to that previously demonstrated over the course of a training year [2]. The physiological perturbations associated with heavy exercise could potentially threaten this stability. The aim of this study was to examine the impact of ultra-endurance triathlon racing on tHb-mass, measured 1-3 hours post-race. Methods Twenty-six male, recreational triathletes were tested on two occasions separated by 2-5 days for measurement of tHb-mass using the optimised CO re-breathing technique [1]. Eighteen of the triathletes (Racers) were rested prior to their first visit and had completed an ultra-endurance triathlon (3.8km swim, 180km bike, 42km run) 1-3 hours prior to their second visit. The remaining eight triathletes (Controls) had undergone no vigorous exercise on either test day. For convenience first and second visits will be referred to as pre-race and post-race for both Racers and Contols. tHb-mass data were log-transformed to reduce bias arising from nonuniformity of error, and are shown below as the back-transformed means and standard deviations (SD). Mean percent change and 90% confidence limits (CL) were calculated for the difference in the change scores (post-race minus pre-race tHb mass) and expressed as the Racers compared with the Controls. If a difference between the groups emerged, it was considered whether this mean percent change was likely greater than 2.2% which is the typical error of measurement (TE) in tHb-mass using the CO re-breathing method in rested athletes [3]. Results The Racers` tHb-mass was 985g ± 134g (mean ± SD) pre-race and 1015g ± 130g post-race. The Controls` tHb-mass was 906g ±118g pre-race and 901g ± 106g post-race. There was a 3.7% (1.8 to 5.7, 90% CL) increase in tHb mass in the racers post-race compared with the Controls. This was a substantial increase in tHb-mass when compared to the normal 2.2% variation in tHb-mass. Figure 1 shows the athletes` individual results. Discussion/Conclusion Contrary to previous findings about tHb-mass stability, ultra-endurance triathlon racing appears to increase tHbmass by ~4%. The question must therefore be posed, where does this extra blood come from? It is unlikely that this amount of haemogloblin can be released from the spleen [4]. It seems more probable that the effect of the racing is not to generate more blood but, instead, to cause physiological changes that confound the accuracy of the tHb-mass calculation used within the optimised CO re-breathing method. The calculations integral to the accuracy of this method make assumptions about the loss of CO to myoglobin (~2% over 7 min) [1] and account successfully for this rate of loss in the rested athlete. However, these assumptions may not hold true post-race due to the release of myoglobin into the circulation from damaged muscle, or increased post-exercise intramuscular blood flow increasing CO loss to myoglobin. Further investigations are required focussing on changes in muscle blood flow following prolonged exercise/racing and its impact on the accuracy of tHb-mass calculation.